가축·비료부문 양분 생성 저감의 경제적 효과 - 권오상; 정학균 (농촌경제, 2021)
This study analyzes the general equilibrium impacts of regulating agricultural phosphorus emissions in Korea. A static computable general equilibrium model is constructed for the analysis. The study introduces a hypothetical phosphorus emission trading scheme that aims to reduce 10 percent of the total emission from the livestock sector in 2015. Scenario 1 of the analysis assumes that both livestock and fertilizer industries are subject to the regulation, while Scenario 2 assumes that only the livestock industry is subject to the regulation. The government’s emission permit revenue is recycled so that farm households maintain their pre-regulation welfare level. The welfare cost of non-farm households is about 0.4 percent of their total expenditure under both scenarios. The result shows that the marginal abatement cost of Scenario 2 is about 50 percent higher than that of Scenario 1. Although those two policy scenarios result in very similar simulated overall welfare impacts, they have substantial differences in industry- specific effects on domestic production, consumer price, and import/ export.